Fuzzy Γ-Hyperideals in Γ-Hypersemirings by Using Triangular Norms - B. A. Ersoy; B. Davvaz; S. Onar; V. Leoreanu-Fotea (The Scientific World Journal)
The concept of Γ-semihyperrings was introduced by Dehkordi and Davvaz as a generalization of semirings, semihyperrings, and Γ-semiring. In this paper, by using the notion of triangular norms, we define the concept of triangular fuzzy sub-Γ-semihyperrings as well as triangular fuzzy Γ-hyperideals of a Γ-semihyperring, and we study a few results in this respect.